2006
DOI: 10.1021/bi052276v
|View full text |Cite
|
Sign up to set email alerts
|

Replication of an Oxidized Abasic Site in Escherichia coli by a dNTP-Stabilized Misalignment Mechanism that Reads Upstream and Downstream Nucleotides

Abstract: Abasic sites (AP) and oxidized abasic lesions are often referred to as noninstructive lesions because they cannot participate in Watson-Crick base pairing. The aptness of the term noninstructive for describing AP site replication has been called into question by recent investigations in E. coli using single-stranded shuttle vectors. These studies revealed that the replication of templates containing AP sites or the oxidized abasic lesions resulting from C1′-(L) and C4′-oxidation (C4-AP) are distinct from one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
5
19
0
Order By: Relevance
“…This frameshift mutation was observed previously for the THF lesion in a 5′-TXG-3′ context, and even higher amounts of this -1 product were obtained when the lesion was 3′ to C (61). Furthermore, recent work from Kroeger and co-workers has shown that replication of a C2′ oxidized abasic site in E. coli relies on a dNTP-stablized primer/template misalignment mechanism to read the bases both upstream and downstream from the abasic site (62). This underscores the importance of the nucleotides surrounding a lesion in determining the outcome of translesion synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…This frameshift mutation was observed previously for the THF lesion in a 5′-TXG-3′ context, and even higher amounts of this -1 product were obtained when the lesion was 3′ to C (61). Furthermore, recent work from Kroeger and co-workers has shown that replication of a C2′ oxidized abasic site in E. coli relies on a dNTP-stablized primer/template misalignment mechanism to read the bases both upstream and downstream from the abasic site (62). This underscores the importance of the nucleotides surrounding a lesion in determining the outcome of translesion synthesis.…”
Section: Discussionmentioning
confidence: 97%
“…The C2′-oxidized abasic site induces mutations in DNA during replication in E. coli via an unusual mechanism that involves the upstream nucleotide (7). Hence, it is imperative that this lesion be repaired.…”
Section: Discussionmentioning
confidence: 99%
“…This includes (but is not limited to) N 2 -acetylaminofluorene (AAF) and N 2 -aminofluorene (AF) modified guanines (80, 162, 177, 226), benzo[ a ]pyrene diol epoxide (BaP) guanine and adenine adducts (129, 162, 208), 8-oxoguanine (8-oxoG) and other guanine oxidation products (141, 163, 164), oxidized abasic lesions (118), N 2 -dG and other acrolein-induced and related adducts (102, 103, 157, 265), butadiene-induced guanine intrastrand and N 2 -N 2 -guanine interstrand crosslinks (41, 121), and alkylated bases (52). By using the single-lesion containing vectors in in vitro reconstituted reactions and by introducing them into strains lacking one or more TLS polymerase, it is straightforward to determine the contribution of each polymerase to the efficiency and accuracy of in vivo lesion bypass.…”
Section: Phenotypes Of E Coli Strains With Deletions Of Pol II Iv Omentioning
confidence: 99%
“…Evidence for the concerted action of SOS-inducible polymerases is also found when assessing TLS of an oxidized abasic site. When the lesion is replicated in E. coli , pol V incorporates dA opposite this lesion producing full-length replication products, while pol II and pol IV utilize a dNTP-stabilized misalignment mechanism to create single-nucleotide deletion products (118). …”
Section: Phenotypes Of E Coli Strains With Deletions Of Pol II Iv Omentioning
confidence: 99%